Modified thermoplastic material and preparation method thereof

By crushing and acidizing corn raw materials, combined with ultrasonic modification of bio-based polymers, the problem of insufficient degradability and mechanical properties of plastic materials is solved, and a high-performance and environmentally friendly modified thermoplastic material is achieved.

CN119875313AActive Publication Date: 2025-04-25DONGGUAN MINGKAI PLASTICS TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510103248.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

The degradability and mechanical properties of existing plastic materials are insufficient, resulting in environmental pollution and application limitations.

Method used

Corn starch is obtained by crushing the corn raw material, mixed with water and natural organic acids, and then ultrasonic modification with bio-based polymer to form a modified thermoplastic material.

Benefits of technology

It improves the mechanical properties, processing stability and degradability of the material, enhances the impact, tensile and compressive resistance of the material, and is suitable for high-performance plastics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875313A_ABST
    Figure CN119875313A_ABST
Patent Text Reader

Abstract

The invention discloses a modified thermoplastic material and a preparation method thereof.The preparation method specifically comprises the steps that a corn raw material is crushed to obtain corn starch, the corn starch and water are mixed according to a preset first mass ratio and then sheared and stirred, and the first water content of a first mixture is obtained; adjusting the second water content of the natural organic acid, and adding the natural organic acid for acidification treatment to obtain a second mixture; wherein the second water content enables the pH value of the second mixture to be in a preset acidification interval and enables the viscosity of the second mixture to be in a preset viscosity interval; mixing the second mixture with a bio-based polymer, and performing ultrasonic treatment modification to obtain a modified component; and mixing the thermoplastic raw material and the modified component according to a preset second mass ratio, and carrying out extrusion molding to obtain the modified thermoplastic material. According to the arrangement, the natural organic acid is utilized to acidify the corn starch, and ultrasonic treatment is matched to obtain the modified component to modify the plastic raw material, so that the performance and the degradability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastics, and in particular to a modified thermoplastic material and a preparation method thereof. Background Art

[0002] Plastic, as one of the most widely used materials in modern society, has the advantages of light weight, good molding and processing, and low cost. Traditional plastics are usually petroleum-based and degrade very slowly. The long-term existence of plastic waste has caused serious pollution to the ecological environment, especially the increasingly serious problem of marine plastic pollution. In order to alleviate this problem, technicians in this field have begun to explore degradable plastics and alternative materials based on biomass resources.

[0003] In recent years, bio-based plastics have gradually gained attention as a potential green alternative. Although they have a lower carbon footprint and better biodegradability, which can effectively reduce the burden of plastic products on the environment, the mechanical properties, thermal stability and processability of bio-based plastics are often poor, which limits their application in the field of high-performance plastics. Therefore, improving the comprehensive performance of bio-based plastics, especially in terms of mechanical properties, processing stability and environmental friendliness, has become an important research direction in the current field of plastic material technology. At the same time, how to improve the degradability and recyclability of traditional plastics through more environmentally friendly means is also a technical problem that technicians in this field need to solve.

[0004] Therefore, it is necessary to develop a new modified thermoplastic material and its preparation method to improve the degradability and mechanical properties of plastics. Summary of the invention

[0005] The purpose of the present invention is to provide a new modified thermoplastic material and a preparation method thereof, so as to solve the problems of poor degradability and insufficient mechanical properties of plastics in the prior art.

[0006] To achieve this object, the present invention adopts the following technical solutions: A method for preparing a modified thermoplastic material, comprising: Step S100, crushing the corn raw material to obtain corn starch, mixing the corn starch and water in a preset first mass ratio, and then shearing and stirring to obtain a first mixture and obtain a first water content of the first mixture; Step S200, adjusting the second water content of the natural organic acid, and adding the natural organic acid for acidification treatment to obtain a second mixture; wherein the second water content makes the pH value of the second mixture within a preset acidification range, and makes the viscosity of the second mixture within a preset viscosity range; Step S300, mixing the second mixture with the bio-based polymer, and then subjecting the mixture to ultrasonic treatment for modification to obtain a modified component; Step S400, mixing the thermoplastic raw material and the modified component according to a preset second mass ratio, and extruding to obtain a modified thermoplastic material; Wherein, the natural organic acid is one of citric acid, acetic acid and succinic acid.

[0007] Optionally, the step S100 specifically includes: Step S110, performing preliminary crushing treatment on the corn raw material to obtain corn particles with a particle size ranging from 300 to 500 microns; Step S120, after mixing corn particles and water in a preset first mass ratio, performing high-pressure shear stirring treatment at a temperature of 60-80° C. to partially dissolve the starch in the corn particles, and adjusting the stirring rate to 500-1000 rpm to uniformly disperse the corn starch and water to form a first mixture; Step S130, pre-cooking the first mixture at a temperature of 80-90° C. to further swell the starch granules, and the pre-cooking time is 5-15 minutes; Step S140, rapidly cooling the pre-ripened first mixture to 40-50° C. to obtain a first mixture; Step S150: measuring the water content of the first mixture.

[0008] Optionally, the step S110 specifically includes: Step S111, preliminarily screening the corn raw material to remove impurities and retain corn kernels with a relatively high degree of integrity; Step S112, preliminarily crushing the corn particles by mechanical crushing equipment, so that the particle size of the crushed corn particles ranges from 200 to 800 microns; Step S113, secondary screening is performed on the preliminarily crushed corn particles to remove particles with a particle size of more than 500 microns, and fine powder with a particle size of less than 300 microns is separated to obtain corn particles with a particle size in the range of 300 to 500 microns; Step S114, mixing the screened corn particles in a low-speed rotating mixer, and introducing a low-flow-rate inert gas during the mixing process.

[0009] Optionally, the step S140 specifically includes: Step S141, quickly transferring the pre-ripened first mixture to a cooling device, and reducing the temperature of the first mixture to 40-50° C. in stages through a pulse cooling system; Step S142: During the cooling process, ultrasonic vibration is applied to the first mixture, with a vibration frequency of 20-50 kHz and a duration of 1-3 minutes.

[0010] Optionally, the step S150 specifically includes: Step S151, inserting a conductivity measuring sensor into the first mixture, measuring the conductivity of the first mixture in real time, and recording the conductivity; Step S152: based on the calibration relationship curve between conductivity and water content, convert the measured conductivity value into the water content of the first mixture to obtain the first water content of the first mixture.

[0011] Optionally, the step S200 specifically includes: S210, calculating the mass of the corn starch and the first water mass according to the mass of the first mixture and the first water content; S220, calculating the target mass of the natural organic acid of the second mixture according to the mass of the corn starch and a preset first matching relationship; calculating the target water mass of the second mixture according to the mass of the corn starch and a preset second matching relationship; and calculating the supplementary water mass according to the difference between the target water mass and the first water mass; S230, calculating a second water content of the natural organic acid according to the target mass of the natural organic acid and the mass of the supplemented water; S240, adjusting the water content of the natural organic acid to a second water content.

[0012] Optionally, the step S300 includes: Step S310, mixing the bio-based polymer and the second mixture according to a preset third mass ratio to obtain a third mixture; Step S320, adjusting the temperature of the third mixture to 50-70° C., and subjecting the third mixture to ultrasonic treatment, wherein the frequency of the ultrasonic treatment is 20-40 kHz, the power density is 30-50 W / cm², and the duration is 5-10 minutes.

[0013] Optionally, before step S320, the method further includes: Step S311, adding a dispersant to the third mixture and stirring, wherein the dispersant is 0.5% to 2.0% by mass of nonylphenol polyoxyethylene ether; After step S320, the method further includes: Step S321: adding 1% to 3% of activated carbon adsorbent by mass to the third mixture, stirring at a rate of 400 to 600 rpm for 3 to 5 minutes, and removing the activated carbon adsorbent by centrifugal separation.

[0014] Optionally, the bio-based polymer is one of polylactic acid, polyhydroxyalkanoate, and bio-based polyamide, and the thermoplastic raw material is thermoplastic polyester or polypropylene.

[0015] A modified thermoplastic material is obtained by the above-mentioned method for preparing the modified thermoplastic material.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The modified thermoplastic material and preparation method thereof provided by the present invention, firstly, corn starch is obtained by crushing corn raw material, then the first mixture is obtained by mixing according to the first mass ratio, and then the natural organic acid is added for acidification, which not only breaks the hydrogen bonds in the starch molecules, but also makes the starch form active side chains with higher free energy in an acidic environment, so that the starch molecules have better reactivity in the subsequent mixing with bio-based polymers, and then are effectively modified under ultrasonic treatment; specifically, under the action of ultrasonic waves, the dispersibility of the modified components is improved, and the cross-linking and bonding between different components are promoted, thereby improving the mechanical properties and processing stability of the material. In the above scheme, corn raw material and natural organic acid are directly used as raw materials, and the renewability is strong, and by adjusting the water content of natural organic acid, the situation that the water content is difficult to estimate after the corn raw material is crushed is overcome, so that the viscosity of the second mixture is in a preset viscosity range, and excessive swelling of corn starch caused by excessive water is prevented, and the viscosity caused by too little water is prevented from being too high and increasing the processing difficulty, thereby improving the performance and degradability of the modified thermoplastic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0018] The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportion or adjustment of size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical contents disclosed by the present invention.

[0019] Figure 1 A schematic flow chart of the method for preparing the modified thermoplastic material provided in this embodiment. DETAILED DESCRIPTION

[0020] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] In the description of the present invention, it should be understood that the terms "upper", "lower", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present invention. It should be noted that when a component is considered to be "connected" to another component, it may be directly connected to the other component or there may be a centrally arranged component at the same time.

[0022] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0023] Embodiment 1: The embodiment of the present invention provides a method for preparing a modified thermoplastic material. By improving the preparation method, a modified thermoplastic material can be obtained. Compared with general plastics, the modified thermoplastic material has higher degradability and performance, which is specifically reflected in mechanical properties, processing stability and environmental friendliness.

[0024] like Figure 1 As shown, the preparation method of the modified thermoplastic material provided in this embodiment includes: Step S100, crushing the corn raw material to obtain corn starch, mixing the corn starch and water at a preset first mass ratio, and then performing high-pressure shear stirring to obtain a first mixture and obtain a first water content of the first mixture; the corn raw material, as a renewable resource, can effectively provide a structural basis for the raw material after crushing, and can create good conditions for a subsequent modification process through operations such as mixing with water, shear stirring, etc.; in this process, the corn starch and water are initially mixed at a first mass ratio, so that the expansion and crystal structure of the starch particles are initially adjusted; Step S200, adjusting the second water content of the natural organic acid, and adding the natural organic acid for acidification treatment to obtain a second mixture; wherein the second water content makes the pH value of the second mixture within a preset acidification range, and makes the viscosity of the second mixture within a preset viscosity range; Next, natural organic acid is added for acidification treatment to enhance the activity of starch molecules. The acidification not only breaks the hydrogen bonds in the starch molecules, but also enables the starch to form active side chains with higher free energy in an acidic environment. It should be noted that since the moisture content of the corn raw material after the crushing process is not adjusted in step S100, it is necessary to accurately adjust the second water content of the natural organic acid in step S200 to maintain the pH value of the second mixture in the preset acidification range and the viscosity of the second mixture in the preset viscosity range, thereby reducing the moisture effect of the corn raw material. This step can save the drying time of the corn raw material, improve production efficiency, and overcome the defect that it is difficult to measure the water content of corn starch.

[0025] Step S300, after mixing the second mixture with the bio-based polymer, perform ultrasonic treatment modification to obtain a modified component; under the action of ultrasound, the internal structure of the material is optimized, the dispersibility of the modified component is improved, and the cross-linking and bonding between different components are promoted, thereby improving the mechanical properties and processing stability of the material.

[0026] Step S400, mixing the thermoplastic raw material and the modified component according to a preset second mass ratio, the second mass ratio is about 1: (3-5), and extruding to obtain a modified thermoplastic material under process conditions of a heating temperature of 180-190° C. and a loading pressure of 12-14 MPa.

[0027] It should be pointed out that after high pressure and acidification treatment, the molecular structure of the modified component is more isotropic, which means that the modified material has a more uniform microstructure, which can not only improve the impact resistance, tensile resistance, compression resistance and shear resistance of the modified thermoplastic material, but also significantly improve the durability and application range of the modified thermoplastic material.

[0028] The natural organic acid is one of citric acid, acetic acid and succinic acid. The selected natural organic acids such as citric acid, acetic acid or succinic acid are environmentally friendly and easily available chemicals. They can not only effectively promote the modification reaction, but also have no adverse effects on the environment, which meets the needs of modern green environmental protection. Through the acidification treatment of this natural organic acid, not only the performance of the material is improved, but also the environmental burden caused by the use of other harmful chemical reagents is avoided.

[0029] In summary, the preparation method of the modified thermoplastic material in the present embodiment, firstly, corn starch is obtained by crushing the corn raw material, then the first mixture is obtained by mixing according to the first mass ratio, and then the natural organic acid is added for acidification, which not only breaks the hydrogen bonds in the starch molecules, but also makes the starch form active side chains with higher free energy in an acidic environment, so that the starch molecules have better reactivity in the subsequent mixing with bio-based polymers, and then are effectively modified under ultrasonic treatment; specifically, under the action of ultrasonic waves, the dispersibility of the modified components is improved, and the cross-linking and bonding between different components are promoted, thereby improving the mechanical properties and processing stability of the material. In the above scheme, corn raw materials and natural organic acids are directly used as raw materials, and the renewability is strong, and by adjusting the water content of natural organic acids, the situation that the water content is difficult to estimate after the corn raw material is crushed is overcome, so that the viscosity of the second mixture is in a preset viscosity range, and excessive swelling of corn starch caused by excessive water is prevented, and the viscosity caused by too little water is also prevented from being too high and increasing the difficulty of processing, thereby improving the performance and degradability of the modified thermoplastic material.

[0030] Furthermore, step S100 specifically includes: Step S110, preliminarily crushing the corn raw material to obtain corn particles with a particle size in the range of 300-500 microns; it should be understood that if the particle size of the corn particles is too large, the starch will not be dissolved enough, and if the particle size is too small, it will easily cause agglomeration. Filtering to obtain corn particles with a particle size in the range of 300-500 microns can ensure that the corn particles can be fully dissolved and dispersed uniformly during the shearing, stirring and pre-cooking process; Step S120, after mixing corn particles and water in a preset first mass ratio, performing high-pressure shear stirring treatment at a temperature of 60-80° C. to partially dissolve corn starch in the corn particles, and adjusting the stirring rate to 500-1000 rpm to uniformly disperse the corn starch and water to form a first mixture; wherein the first mass ratio is preferably 1:4 in this embodiment, and in other optional embodiments, it may be 1:(3.5-4.5); It should be noted that the high-pressure shearing and stirring treatment is achieved by a high-pressure shearing and stirring device, which is mainly composed of a high-pressure reactor, a stirring system and a heating system. The above structure is well known to those skilled in the art and is not specifically described in this embodiment. The high-pressure reactor can withstand a relatively high internal pressure (for example, 1 to 5 MPa), and the stirring system can achieve high-speed shearing (500 to 1000 rpm), which can effectively disperse the material and promote the dissolution of corn starch.

[0031] Step S130, pre-cooking the first mixture at a temperature of 80-90°C, so that the granular structure of the corn starch is further expanded, and its crystal structure is partially destroyed, so as to form a first mixture with preliminary rheological properties, wherein the pre-cooking time is 5-15 minutes; in this step, the granular structure of the corn starch in the first mixture is further expanded, and its crystal structure is partially destroyed, so as to form a first mixture with preliminary rheological properties. Within this temperature range, the crystallized region of the granular structure is destroyed, the internal hydrogen bonds are partially broken, and a molecular structure with higher reactivity is formed, and the pre-cooking time control ensures that the granular structure of the corn starch will not fail to fully expand due to too short a time, nor will it be over-gelatinized due to too long a time, which will affect its subsequent interaction with natural organic acids and bio-based polymers.

[0032] It should be noted that the pre-cooking treatment is achieved through pre-cooking equipment, which is a heating tank or a continuous pre-cooking machine, and is equipped with a stirring device to ensure that the material is heated evenly.

[0033] Step S140, rapidly cool the pre-ripened first mixture to 40-50°C to obtain a first mixture; this cooling process can stabilize the molecular structure of the adjusted corn starch and prevent starch degradation or viscosity change caused by spontaneous reaction under high temperature. At the same time, this cooling temperature range also provides suitable environmental conditions for subsequent water content measurement, avoiding measurement errors caused by excessively high temperature; Step S150: measuring the water content of the first mixture.

[0034] More specifically, step S110 includes: Step S111, preliminarily screening the corn raw materials, removing impurities and retaining corn raw materials with higher integrity; Preliminarily screening the corn raw materials, removing impurities and retaining corn raw materials with higher integrity, this process can effectively remove foreign impurities such as sand, gravel, straw, etc. in the corn raw materials, while ensuring the consistency of the selected corn raw materials in physical properties and chemical composition, which is helpful to improve the processing stability and reaction efficiency of the particles in the subsequent processing process; Step S112, the corn raw material is preliminarily crushed by mechanical crushing equipment, so that the particle size of the crushed corn particles ranges from 200 to 800 microns; in this process, the corn raw material is crushed into corn particles, and the corn particles contain corn starch; among them, too large a particle size will lead to reduced screening efficiency, and at the same time it is not conducive to the uniform dissolution of starch particles in subsequent processing; too small a particle size is easy to cause agglomeration, which increases the difficulty of the dispersion and mixing process. By reasonably adjusting the tool gap and rotation speed of the crushing equipment, corn particles with uniform crushing effect can be obtained, which significantly improves the consistency of the raw materials.

[0035] Step S113, the initially crushed corn particles are subjected to secondary screening to remove particles with a particle size exceeding 500 microns, and to separate fine powder with a particle size below 300 microns, to obtain corn particles with a particle size ranging from 300 to 500 microns; the above arrangement can prevent the performance of the particles from being degraded due to oxidation during the mixing process.

[0036] Step S114, the screened corn particles are mixed in a low-speed rotating mixer, and an inert gas with a low flow rate is introduced during the mixing process to obtain corn particles that are viscous as a whole. The introduction of the inert gas can effectively isolate the oxygen and moisture in the air. At the same time, the low-speed rotating mixer can ensure that the particles reach a highly uniform mixing state without being damaged by excessive mechanical force. This process not only improves the storage stability of the corn particles, but also makes the performance of the corn particles more stable in subsequent processing.

[0037] It should be noted that, considering that the second water content of the natural organic acid needs to be adjusted in the subsequent steps, there is no need to dry the water in advance in the above steps, and corn particles in a viscous or pasty state can be directly obtained, thereby improving the processing efficiency of the corn raw material. At the same time, not only the process flow is simplified, but also the risk of increased energy consumption and changes in raw material properties caused by unnecessary drying steps is effectively avoided, so that the corn particles can better maintain the integrity of their particle structure during the initial crushing and mixing process, and avoid the problem of brittle particles or excessive powdering due to water loss. In addition, since the subsequent steps accurately control the viscosity and equilibrium state of the system by adjusting the second water content of the natural organic acid, the corn raw material that has not been dried can better form a uniformly distributed mixed system with the natural organic acid, providing ideal initial conditions for the acidification reaction. The problem of incomplete expansion or poor dispersibility of starch particles caused by insufficient water is avoided, and the phenomenon of decreased efficiency of the acidification reaction or unstable viscosity caused by excessive water is also prevented.

[0038] In addition, the above-mentioned mechanical crushing equipment includes but is not limited to a hammer mill, a toothed roller mill or a ball mill; the above-mentioned screening equipment for screening includes but is not limited to a vibrating screen, a cyclone screen and a centrifugal screen, etc. The difference in each screening is that the mesh size of the screen is different; the mixer includes but is not limited to a V-type mixer, a double-cone mixer or a spiral belt mixer, etc., which are mainly used to mix corn particles.

[0039] More specifically, step S140 includes: Step S141, quickly transfer the pre-matured first mixture to a cooling device, and reduce the temperature of the first mixture to 40-50°C in stages through a pulse cooling system; the pulse cooling system is an indirect refrigeration device that can intermittently introduce a cooling medium, which is well known to those skilled in the art and is not specifically introduced in this embodiment.

[0040] Step S142: During the cooling process, ultrasonic vibration is applied to the first mixture, with a vibration frequency of 20-50 kHz and a duration of 1-3 minutes.

[0041] It can be understood that the pulse cooling system avoids the uneven temperature gradient and particle agglomeration caused by rapid cooling in traditional cooling methods by lowering the temperature in stages, while ensuring that the first mixture maintains stable viscosity and rheological properties in the process of cooling from high temperature to 40~50℃; the introduction of ultrasonic vibration further enhances the particle dispersion effect during the cooling process, and its high-frequency vibration of 20~50kHz destroys the weak aggregation force between particles through cavitation effect and microflow effect, so that the first mixture forms a more uniform dispersion state, thereby improving the consistency and stability of its internal structure; through the above settings, not only the stability and efficiency of the cooling process are improved, but also a higher quality raw material basis is provided for subsequent acidification and modification operations, which significantly improves the mechanical properties and production consistency of modified thermoplastic materials.

[0042] More specifically, step S150 includes: Step S151, inserting a conductivity measuring sensor into the first mixture, measuring the conductivity of the first mixture in real time, and recording the conductivity value; Step S152: based on the calibration relationship curve between conductivity and water content, convert the measured conductivity value into the water content of the first mixture to obtain the first water content of the first mixture.

[0043] It is understandable that changes in water content will significantly affect the overall conductivity of the mixture. Specifically, as the amount of water in the mixture increases, the conductivity will increase, and vice versa. Therefore, by measuring the conductivity and based on the pre-calibrated conductivity-water content relationship curve, the water content of the mixture can be calculated more accurately and efficiently, avoiding the error problems caused by cumbersome operations or measurement lags in traditional methods. It should be noted that the calibration relationship curve between conductivity and water content can be obtained by experimental measurement. The specific acquisition method is to prepare a series of standard samples with known water content, control the moisture content range (such as 10%~35%) and measure their conductivity values ​​under constant temperature conditions, draw a scatter plot of conductivity-water content and perform curve fitting, establish a mathematical relationship model between the two, and obtain a calibration relationship curve between conductivity and water content.

[0044] Further, step S200 specifically includes: S210, calculating the mass of the corn starch and the first water mass according to the mass M1 and the first water content C1 of the first mixture; Specifically, the mass of corn starch M11=M1×(1-C1); the mass of first water M12=M1×C1; S220, calculating the target mass M21 of the natural organic acid of the second mixture according to the mass M11 of the corn starch and the preset first matching relationship; calculating the target water mass M13 of the second mixture according to the mass M11 of the corn starch and the preset second matching relationship; and calculating the supplementary water mass M22 according to the difference between the target water mass M13 and the first water mass M12; Among them, the first matching relationship and the second matching relationship can be obtained through advance experiments, which reflect the different qualities of corn starch, the amount of natural organic acid and water required, so that the pH value of the second mixture is in the preset acidification range, and the viscosity of the second mixture is in the preset viscosity range. For reference, the preset acidification range is 3.0~5.0, and the preset viscosity range is 1000 mPa·s~3000 mPa·s. For example, the first matching relationship and the second matching relationship can be determined by the sample method, by preparing multiple groups of corn starch samples of different masses, under the same corn starch mass, each group of samples corresponding to multiple groups of different pH values ​​and viscosities, correspondingly, there are required water and natural organic acid amounts, and then the acidified corn starch is processed in subsequent steps to select the best modified thermoplastic material, so as to find out the required water and natural organic acid amount under the corn starch mass; by repeating the above-mentioned samples for multiple groups of corn starch of different masses, the water and natural organic acid amount corresponding to the corn starch of different masses, that is, the corresponding pH value range and viscosity range can be found, thereby determining the first matching relationship and the second matching relationship. By finding its optimal pH value range and viscosity range, that is, the above ranges are judged by the modified thermoplastic material prepared from the sample, and by finding out in which pH value range and viscosity range the corn starch sample of a certain mass is located, the performance of the modified thermoplastic material obtained can be better, thereby determining the concentration of natural organic acid that needs to be supplemented in the corn starch sample, thereby finding out the water and natural organic acid amount required for corn starch of different masses, which is convenient for the subsequent rapid determination of the amount of water required for the natural organic acid.

[0045] S230, calculating the second water content C2 of the natural organic acid according to the target mass M21 of the natural organic acid and the mass M22 of the supplementary water; the second water content C2=M22 / (M21+M22); S240, adjusting the water content of the initial natural organic acid to a second water content C2.

[0046] The core of the above steps is to provide the conditions required for acidification for the second mixture of different mass and water content through fitting methods well known to those skilled in the art, such as the sample method and the table method, so as to facilitate those skilled in the art to adjust the concentration or ratio of the natural organic acid, thereby preventing the pH value and viscosity from failing to meet the standards during subsequent processing, thereby avoiding the degradation of the performance of the modified thermoplastic material.

[0047] Further, step S300 includes: Step S310, mixing the bio-based polymer and the second mixture at a preset third mass ratio to obtain a third mixture; wherein the third mass ratio is 1:(4-6), and in this embodiment, preferably 1:5; Step S320, adjusting the temperature of the third mixture to 50-70° C., and subjecting the third mixture to ultrasonic treatment, wherein the frequency of the ultrasonic treatment is 20-40 kHz, the power density is 30-50 W / cm², and the duration is 5-10 minutes.

[0048] Among them, the temperature control of 50~70℃ can significantly reduce the viscosity of the third mixture, so that the dispersion of the bio-based polymer in the second mixture is more uniform; under the above-mentioned appropriate temperature increase environment, the fluidity of the corn starch molecular chain increases, and the interface effect between the natural organic acid molecules and the bio-based polymer is further strengthened, providing an ideal dispersion basis for ultrasonic treatment. Secondly, the temperature range of 50~70℃ is in the partial softening range of the bio-based polymer, and is lower than the thermal degradation temperature of corn starch and natural organic acids; within this temperature range, the molecular chain of the bio-based polymer begins to stretch, and will not cause molecular chain breakage or side reactions due to excessive temperature; that is, the expansion degree of corn starch is also controlled within a reasonable range, which not only increases the interaction area with the bio-based polymer, but also avoids the instability of the mixture structure caused by excessive expansion, which can achieve the optimization of the material structure at the molecular scale and provide a stable basis for subsequent modification.

[0049] Furthermore, before step S320, the following steps are also included: Step S311, adding a dispersant to the third mixture and stirring, wherein the dispersant is 0.5% to 2.0% by mass of nonylphenol polyoxyethylene ether; the ratio of the dispersant to the third mixture is about 1: (50 to 60); After step S320, the method further includes: Step S321: adding 1% to 3% of activated carbon adsorbent by mass to the third mixture, stirring at a rate of 400 to 600 rpm for 3 to 5 minutes, and removing the activated carbon adsorbent by centrifugal separation.

[0050] It should be noted that the dispersant can significantly reduce the interfacial tension between the bio-based polymer and the second mixture, improve the dispersion state of the two-phase system, make the ultrasonic treatment more efficient, and make the molecular chain breakage and recombination more uniform, and finally improve the mechanical properties and stability of the modified component. After removing the dispersant in step S321, the environmental problems caused by the dispersant can be reduced.

[0051] Among them, the bio-based polymer is one of polylactic acid, polyhydroxyalkanoate, and bio-based polyamide, and the thermoplastic raw material is thermoplastic polyester or polypropylene. Exemplary: 1. The bio-based polymer is polylactic acid (PLA), and the thermoplastic raw material is thermoplastic polyester; in step S300, polylactic acid and the second mixture are fully mixed under the action of ultrasound to form a uniform modified component, which promotes cross-linking and bonding between molecules; under the high temperature and high pressure conditions of step S400, the modified component is further melt-blended with the thermoplastic polyester to form a modified thermoplastic material with excellent mechanical properties, which is suitable for application scenarios requiring high strength and environmental protection; 2. The bio-based polymer is polyhydroxyalkanoate (pHA), and the thermoplastic raw material is polypropylene. After acidification and ultrasonic modification, the molecular chains of polyhydroxyalkanoate form a closer interaction in the modified component; poly The addition of propylene improves the melt index and processing performance of the material; the modified thermoplastic material has good toughness, heat resistance and degradability, and is suitable for the fields of film, packaging materials, etc.; 3. The bio-based polymer uses bio-based polyamide, and the thermoplastic raw material uses thermoplastic polyester; in step S300, the bio-based polyamide and the second mixture undergo effective interface fusion under the action of ultrasound to form a modified component with uniform structure; in the subsequent extrusion molding process, the microstructure of the material is optimized and exhibits isotropic characteristics; this combination makes the modified thermoplastic material have excellent tensile resistance, impact resistance and wear resistance, and is suitable for the application of high-performance engineering plastics, such as automotive parts, electronic equipment housings, etc. The above settings indicate the combination of the modified component and the thermoplastic raw material in this embodiment, and provide optional solutions for different types of usage scenarios.

[0052] Embodiment 2: This embodiment also provides a modified thermoplastic material, which is prepared by the preparation method in embodiment one.

[0053] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a modified thermoplastic material, characterized in that: include: Step S100, crushing the corn raw material to obtain corn starch, mixing the corn starch and water in a preset first mass ratio, and then shearing and stirring to obtain a first mixture and obtain a first water content of the first mixture; Step S200, adjusting the second water content of the natural organic acid, and adding the natural organic acid for acidification treatment to obtain a second mixture; wherein the second water content makes the pH value of the second mixture within a preset acidification range, and makes the viscosity of the second mixture within a preset viscosity range; Step S300, mixing the second mixture with the bio-based polymer, and then subjecting the mixture to ultrasonic treatment for modification to obtain a modified component; Step S400, mixing the thermoplastic raw material and the modified component according to a preset second mass ratio, and extruding to obtain a modified thermoplastic material; Wherein, the natural organic acid is one of citric acid, acetic acid and succinic acid.

2. The method for preparing a modified thermoplastic material according to claim 1, characterized in that: The step S100 specifically includes: Step S110, performing preliminary crushing treatment on the corn raw material to obtain corn particles with a particle size ranging from 300 to 500 microns; Step S120, after mixing corn particles and water in a preset first mass ratio, performing high-pressure shear stirring treatment at a temperature of 60-80° C. to partially dissolve the starch in the corn particles, and adjusting the stirring rate to 500-1000 rpm to uniformly disperse the corn starch and water to form a first mixture; Step S130, pre-cooking the first mixture at a temperature of 80-90° C. to further swell the starch granules, and the pre-cooking time is 5-15 minutes; Step S140, rapidly cooling the pre-ripened first mixture to 40-50° C. to obtain a first mixture; Step S150: measuring the water content of the first mixture.

3. The method for preparing a modified thermoplastic material according to claim 2, characterized in that: The step S110 specifically includes: Step S111, preliminarily screening the corn raw materials to remove impurities and retain corn raw materials with higher integrity; Step S112, preliminarily crushing the corn raw material by mechanical crushing equipment, so that the particle size of the crushed corn particles ranges from 200 to 800 microns; Step S113, secondary screening is performed on the preliminarily crushed corn particles to remove particles with a particle size of more than 500 microns, and fine powder with a particle size of less than 300 microns is separated to obtain corn particles with a particle size in the range of 300 to 500 microns; Step S114, mixing the screened corn particles in a low-speed rotating mixer, and introducing a low-flow inert gas during the mixing process.

4. The method for preparing a modified thermoplastic material according to claim 2, characterized in that: The step S140 specifically includes: Step S141, quickly transferring the pre-ripened first mixture to a cooling device, and reducing the temperature of the first mixture to 40-50° C. in stages through a pulse cooling system; Step S142: During the cooling process, ultrasonic vibration is applied to the first mixture, with a vibration frequency of 20-50 kHz and a duration of 1-3 minutes.

5. The method for preparing a modified thermoplastic material according to claim 2, characterized in that: The step S150 specifically includes: Step S151, inserting a conductivity measuring sensor into the first mixture, measuring the conductivity of the first mixture in real time, and recording the conductivity; Step S152: based on the calibration relationship curve between conductivity and water content, convert the measured conductivity value into the water content of the first mixture to obtain the first water content of the first mixture.

6. The method for preparing a modified thermoplastic material according to claim 2, characterized in that: The step S200 specifically includes: S210, calculating the mass of the corn starch and the first water mass according to the mass of the first mixture and the first water content; S220, calculating the target mass of the natural organic acid of the second mixture according to the mass of the corn starch and a preset first matching relationship; calculating the target water mass of the second mixture according to the mass of the corn starch and a preset second matching relationship; and calculating the supplementary water mass according to the difference between the target water mass and the first water mass; S230, calculating a second water content of the natural organic acid according to the target mass of the natural organic acid and the mass of the supplemented water; S240, adjusting the water content of the natural organic acid to a second water content.

7. The method for preparing a modified thermoplastic material according to claim 1, characterized in that: The step S300 includes: Step S310, mixing the bio-based polymer and the second mixture according to a preset third mass ratio to obtain a third mixture; Step S320, adjusting the temperature of the third mixture to 50-70° C., and subjecting the third mixture to ultrasonic treatment, wherein the frequency of the ultrasonic treatment is 20-40 kHz, the power density is 30-50 W / cm², and the duration is 5-10 minutes.

8. The method for preparing a modified thermoplastic material according to claim 7, characterized in that: Before step S320, the method further includes: Step S311, adding a dispersant to the third mixture and stirring, wherein the dispersant is 0.5% to 2.0% by mass of nonylphenol polyoxyethylene ether; After step S320, the method further includes: Step S321: adding 1% to 3% of activated carbon adsorbent by mass to the third mixture, stirring at a rate of 400 to 600 rpm for 3 to 5 minutes, and removing the activated carbon adsorbent by centrifugal separation.

9. The method for preparing a modified thermoplastic material according to claim 1, characterized in that: The bio-based polymer is one of polylactic acid, polyhydroxyalkanoate, and bio-based polyamide, and the thermoplastic raw material is thermoplastic polyester or polypropylene.

10. A modified thermoplastic material, characterized in that: The modified thermoplastic material is obtained by the method for preparing the modified thermoplastic material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of fully biodegradable starch / polylactic acid base resin

    CN105440606A

  • PBAT / modified starch full-biodegradable film with high ductility and high barrier property, and preparation method and application thereof

    CN108929527A

  • Production process of biodegradable environment-friendly plastic

    CN119161619A

  • Starchy food-based fine particle fat substitute

    WO2000022939A2